PEMBINAAN FINANCIAL REPORT MENGGUNAKAN APLIKASI LAMIKRO DAN PROMOSI ONLINE PADA KRE CELL - Viola Syukrina E Janrosl; Triana Amanda Rustan; Neni Marlina Br Purba (Jurnal Pengabdian Ibnu Sina, 2022)
An increasingly dynamic era forces every individual to be more creative in seeking opportunities in the intense economic competition. In order to balance all conditions, we are required to work hard in order to increase the economy and the welfare of workers. Things you can do, start from opening your own business or joining a partner. In this digital era, accounting applications are strongly recommended to be used by SME business actors so that micro SMEs in Indonesia can monitor all SME financial activities. The Lamikro application provides flexible and easy-to-use access, with many user-based options. Mr. Chaef is the owner whose address is Mr. chaef is the owner of KRE Cell having his address at Pasar Aviari Blok D2 no 1 has not yet implemented accounting in his business. This business only makes business expenses and income manually so that if employees commit fraud it is difficult to detect it. The decline in sales in the Covid-19 era has made this business need an injection of funds from banks, but it is hampered by the absence of financial reports for this business. KRE Cell's Statement of Financial Position and Profit and Loss has been prepared using the Lamikro Application. Although the background of business actors is not in the accounting field, they have a desire to study the Lamikro application related to the preparation of financial reports. The KRE Cell business actor has recorded transactions using the Lamikro application. The results have been achieved from the implementation of the first development of the KRE Cell financial position and profit and loss statements that have been compiled with the Lamikro Application. Although business actors do not come from accounting, they want to learn the use of applications in compiling financial reports for the reason that it is easier and faster. KRE Cell business actors have recorded transactions using the Lamikro Application. KRE Cell business actors understand promotion and marketplace using social media, namely using Facebook, Instagram.